1995
DOI: 10.1159/000139273
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mucosa in the in vitro Changes in Guinea Pig Bladder Function Which Occur after Sensitization with Ovalbumin

Abstract: Bladder strips from sensitized guinea pigs respond to ovalbumin challenge with a contraction accompanied by release of histamine, prostaglandin, and leukotriene. Histamine and prostaglandin release occurs preferentially from the bladder mucosa, while leukotrienes are released by the smooth muscle. This study investigated the effects of removal of the bladder mucosa on contractile responses of strips from control and sensitized guinea pigs to electrical stimulation and to contractile agonists. Removal of the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Thus, the strips without mucosa responded to electrical field stimulation (EFS), bethanechol, ATP, and KCl significantly greater than the strips with mucosa, which suggest an inhibitory role of the urothelium in the control of bladder contractility (13). This is in agreement with another study performed by the same group in guinea pig bladder (12). Although the urothelium differs from the colonic mucosa in its absorptive properties, both layers contact with smooth muscle layers whose activation propels contents.…”
supporting
confidence: 89%
“…Thus, the strips without mucosa responded to electrical field stimulation (EFS), bethanechol, ATP, and KCl significantly greater than the strips with mucosa, which suggest an inhibitory role of the urothelium in the control of bladder contractility (13). This is in agreement with another study performed by the same group in guinea pig bladder (12). Although the urothelium differs from the colonic mucosa in its absorptive properties, both layers contact with smooth muscle layers whose activation propels contents.…”
supporting
confidence: 89%
“…To date, little is known about the role of AKR1C3 in the urothelium. The urothelium has been shown to be the main source of PGs within the bladder (Krasnopolsky et al 1995), and it has been The Journal of Histochemistry & Cytochemistry AKR1C3 in the Genitourinary System suggested that these PGs could be related to a stretch sensing role during bladder filling (Azadzoi et al 2004;Schroder et al 2004;de Jongh et al 2007). Alternate roles for AKR1C3, and its rat homolog, in the bladder could be for the creation of a watertight barrier for confining urine and as a possible regulator controlling the inflammatory effects of urine (Oleksiewicz et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mucosa‐dependent inhibition, removal of the mucosa has also been shown to decrease the contractile response to muscarinic receptor stimulation, electrical field stimulation, and ATP, or to have no effect on the response to electrical field stimulation, carbachol, and KCl in the rat bladder. Similarly, in the guinea pig, the presence of the mucosa did not affect (or slightly increased) the response to histamine, bethanechol, KCl, and electrical stimulation . Moreover, a non‐adrenergic, non‐nitrergic, non‐prostanoid relaxant agent that does not originate from the mucosa was reportedly released by stimulation of muscarinic receptors in the detrusor, suggesting an inhibitory factor may also be produced by bladder tissue during contraction …”
Section: Introductionmentioning
confidence: 89%